Homeless Deaths in Eskişehir 10 Years Experience - Çelikel, Adnan; Karbeyaz, Kenan; Düzer, Selma; Akkaya, Harun; Ortanca, İbrahim and Balcı, Yasemin (The Bulletin of Legal Medicine, 2015)
Objective: Homelessness is a major social problem that can be seen in all societies. The causes of homelessness indicate changes according to the society. Eskişehir is in the western region of the Anatolia, where is known as high socioeconomic level and a student city. The aim of this study is to present the homeless deaths data by analyzing and comparing with the literature in Eskişehir. Materials and Methods: We retrospectively analyzed 3108 autopsy between 2004 and 2013 in Eskişehir. Considering autopsy reports and judicial investigation identified 34 homeless deaths and included in the study. Results: Ten years period covered and it was found that 1.1% of the forensic deaths were homeless death. The cases were mostly 40-50 age group (38.2 %) and 91.2% were male. It was determined that 61.8% died of the natural reasons. Conclusion: Consequently, this study demonstrated that homelessness is a problem in our city. A significant portion of the homeless people is passed away from curable and preventable reasons. To prevent homeless deaths, homeless people should be recorded and be supported health and social lives. Investigations must be carefully analyzed in homeless deaths. Autopsy and necessary tests should be performed. Keywords: Homeless, Forensic medicine, Autopsy.